Ontology-based applications for enterprise systems and knowledge management - Ahmad, Mohammad Nazir, 1976-; Colomb, Robert M., 1942-; Abdullah, Mohd Syazwan, 1973- (Hershey, PA : Information Science Reference, 2013)
'This book provides an opportunity for readers to clearly understand the notion of ontology engineering and the practical aspects of this approach in the domains of two interest areas: Knowledge Management Systems and Enterprise Systems'--
'Premier reference source'--Cover.
Includes bibliographical references and index. 358-410
Keywords: Expert systems (Computer science).; Knowledge management; Business enterprises -- Computer networks; Ontology